Implementing integrated reporting to disclose intellectual capital in health organisations: a case study. Issue 2 (30th July 2020) - Dameri, Renata Paola; Ferrando, Pier Maria
Abstract : Purpose: The aim of our research is to give empirical and theoretical solutions to some criticalities of the original International Integrated Reporting Framework (IIRF). Indeed, it takes as value creation only the increase of the capitals triggered by business activities, overlooking the fulfilment of the institutional mission that is the actual value creation lever. Design/methodology/approach: The present paper introduces a case study aimed at implementing the IIRF in an Italian non-profit healthcare organisation. The research is based on theory building from cases, action research and interventionist approach. IIRF was adopted because of its claimed ability to support the communication process to stakeholders and the control of value creation. However, IIRF shows several weaknesses. Findings: An adjusted version of IIRF is suggested, highlighting the role played by IC in the organisational business model and in the value creation process. The adjusted seems able to foster awareness of the role IC in value creation in healthcare organisations. Research limitations/implications: In this paper no one of the singles pieces of the adjusted framework is innovative by itself, but jointly they give raise to an innovative solution, able to address the disclosing and managerial needs of the examined organisation. The single case study permits to us to test the weaknesses of the IIRF claimed in the literature, to suggest some adjustments to the original framework and to validate their effectiveness. Thanks to the single case study we then built theoretical constructs developing theory inductively; now the suggested framework can be further tested and validated in other organisations. Originality/value: The paper introduces an innovative approach to IC reporting and disclosure in healthcare organisations. This is relevant not only for external communication but also for internal aims supporting managers in decision and actions.